Assimilating satellite‐based canopy height within an ecosystem model to estimate aboveground forest biomass. Issue 13 (11th July 2017) - Joetzjer, E.; Pillet, M.; Ciais, P.; Barbier, N.; Chave, J.; Schlund, M.; Maignan, F.; Barichivich, J.; Luyssaert, S.; Hérault, B.; von Poncet, F.; Poulter, B.
Abstract: Despite advances in Earth observation and modeling, estimating tropical biomass remains a challenge. Recent work suggests that integrating satellite measurements of canopy height within ecosystem models is a promising approach to infer biomass. We tested the feasibility of this approach to retrieve aboveground biomass (AGB) at three tropical forest sites by assimilating remotely sensed canopy height derived from a texture analysis algorithm applied to the high‐resolution Pleiades imager in the Organizing Carbon and Hydrology in Dynamic Ecosystems Canopy (ORCHIDEE‐CAN) ecosystem model. While mean AGB could be estimated within 10% of AGB derived from census data in average across sites, canopy height derived from Pleiades product was spatially too smooth, thus unable to accurately resolve large height (and biomass) variations within the site considered. The error budget was evaluated in details, and systematic errors related to the ORCHIDEE‐CAN structure contribute as a secondary source of error and could be overcome by using improved allometric equations. Key Points: The global ORCHIDEE ecosystem model is suitable for assimilating remotely sensed forest structure data to estimates AGB in tropical forests The FOTO‐Pleiades products used for the assimilation system bear too large systematic errors to retrieve the fine‐scale structure of AGB Most of the systematic errors related to ORCHIDEE‐CAN could be reduced by improving the allometric equations